PENGEMBANGAN MODEL MASPRO (MASALAH DAN PROYEK) BERBASIS TPACK UNTUK MENINGKATKAN KREATIFITAS PESERTA DIDIK PADA MATA PELAJARAN PKN - Atik Kurnia Jayanti; Sutrisno Wibawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Nowadays, many student-centered learning models have been developed. However, there is no learning model that combines problem-based and project-based. The author found a MASPRO (Problems and Projects) learning model to overcome various problems in learning.. This research has reached the development stage. The subjects of this research were 2 learning material experts, 3 teachers and 10 students. This learning mode is correlated with different problems in the 3 lessons. The object of this research is validation of the MASPRO learning model. Data collection using the questionnaire method using the Ima scale, and data analysis using the percentage formula. The percentage results from expert tests, media, and learning model effectiveness were respectively 96%, 93%, 88% with very good qualifications.